Autobiographical reflections part II: risk, tenacity and philosophies of research. (21st August 2017) - Tadajewski, Mark; Jones, Brian
Abstract : Purpose: This paper reviews autobiographical accounts of thought leadership in the marketing discipline and draws out pertinent insights for senior, mid-career and junior academics alike. Design/methodology/approach: This narrative is based on a close reading of the pertinent material. Findings: To be a pioneer in marketing takes considerable hard work, tenacity, serendipity, and a high tolerance for risk. Originality/value: This manuscript can be used by junior scholars to legitimize the challenges they pose to more established colleagues. It helps contribute to the reversal of extant power relations in academic practice.